AN ALTERNATIVE DEA APPROACH FOR EVALUATING THE SYSTEM EFFICIENCY IN THE PRESENCE OF DUAL-ROLE FACTORS - Jahani Sayyad Noveiri, Monireh; Kordrostami, Sohrab; Amirteimoori, Alireza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In evaluating the performance of production systems, the role of a measure from input and output aspects is usually certain and known. Nevertheless, there are occasions in the real world that some factors can play both input and output roles. In data envelopment analysis (DEA) literature, these factors are called dual-role factors. In the current paper, an alternative DEA approach is proposed for incorporating dual-role factors in the production process. In previous models, a dual-role factor can only take one role (input, output or indifference to being an input or an output) after the evaluation while in the proposed model herein a dual-role factor can simultaneously take both input role and output role in estimating the efficiency of each decision making unit (DMU). Indeed, a portion of a dual-role factor is obtained as a mixture of input and output roles. Numerical examples are used to illustrate the suggested approach.